John the Evangelist and medieval German writing imitating the inimitable - Volfing, Annette (Oxford University Press, 2001)
John the Evangelist is the focus of this spiritual and literary discussion in a range of Middle High German writings. This study contributes to our understanding of German literature and the history of Western spirituality.